Biophotonic endoscopy: a review of clinical research techniques for optical imaging and sensing of early gastrointestinal cancer - Coda, Sergio; Siersema, Peter D.; Stamp, Gordon W. H.; Thillainayagam, Andrew V. (Endoscopy International Open, 2015)
Detection, characterization, and staging constitute the fundamental elements in the endoscopic diagnosis of gastrointestinal diseases, but histology still remains the diagnostic gold standard.New developments in endoscopic techniques may challenge histopathology in the near future. An ideal endoscopic technique should combine a wide-field, “red flag” screening technique with an optical contrast or microscopy method for characterization and staging, all simultaneously available during the procedure. In theory, biophotonic advances have the potential to unite these elements to allow in vivo “optical biopsy.”These techniques may ultimately offer the potential to increase the rates of detection of high risk lesions and the ability to target biopsies and resections, and so reduce the need for biopsy, costs, and uncertainty for patients. However, their utility and sensitivity in clinical practice must be evaluated against those of conventional histopathology.This review describes some of the most recent applications of biophotonics in endoscopic optical imaging and metrology, along with their fundamental principles and the clinical experience that has been acquired in their deployment as tools for the endoscopist. Particular emphasis has been placed on translational label-free optical techniques, such as fluorescence spectroscopy, fluorescence lifetime imaging microscopy (FLIM), two-photon and multi-photon microscopy, second harmonic generation (SHG) and third harmonic generation (THG) imaging, optical coherence tomography (OCT), diffuse reflectance, Raman spectroscopy, and molecular imaging.